1990
DOI: 10.1111/j.1432-1033.1990.tb15448.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for variable metal‐radical spin coupling in oxoferrylporphyrin cation radical complexes

Abstract: Oxoferrylporphyrin cation radical complexes were generated by m-chloroperoxybenzoic acid oxidation of the chloro and trifluoromethanesulfonato complexes of tetramesitylporphyrinatoiron(II1) [(TMP)Fe] and the trifluoromethanesulfonato complex of tetra(2,6-dichlorophenyl)porphyrinatoiron(IlI) [TPP(2,. Coupling between ferry1 iron (S = 1) and porphyrin radical (S' = 1/2) spin systems was investigated by Mossbauer and EPR spectroscopy. The oxoferrylporphyrin cation radical systems generated from the TMP complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
28
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 46 publications
6
28
0
Order By: Relevance
“…Computational studies based on the crystal structure gave a calculated absorption spectrum (Figure S16) that is in qualitative agreement with the experimental spectra shown in Figure B. The frozen solution X-band EPR spectrum at 77 K in CH 3 CN (Figure C) is characteristic of a S = 3/2 species. , Quinuclidine and excess (dtbbpy)NiCl 2 were essential in forming this compound since their absence in the reaction between Ni(0) and Ni(II) led to a decomposition product (Figures S11 and S12), consistent with the increased stability observed by TA spectroscopy (Figure S2).…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Computational studies based on the crystal structure gave a calculated absorption spectrum (Figure S16) that is in qualitative agreement with the experimental spectra shown in Figure B. The frozen solution X-band EPR spectrum at 77 K in CH 3 CN (Figure C) is characteristic of a S = 3/2 species. , Quinuclidine and excess (dtbbpy)NiCl 2 were essential in forming this compound since their absence in the reaction between Ni(0) and Ni(II) led to a decomposition product (Figures S11 and S12), consistent with the increased stability observed by TA spectroscopy (Figure S2).…”
supporting
confidence: 72%
“…The frozen solution X-band EPR spectrum at 77 K in CH 3 CN (Figure 2C) is characteristic of a S = 3/2 species. 19,20 Quinuclidine and excess (dtbbpy)NiCl 2 were essential in forming this compound since their absence in the reaction between Ni(0) and Ni(II) led to a decomposition product (Figures S11 and S12), consistent with the increased stability observed by TA spectroscopy (Figure S2).…”
supporting
confidence: 66%
“…50,52 However, Krik and co-workers later reported that Cmpd I of this system could in fact be generated in nonpolar solvents under the same experimental conditions, in the presence of axially coordinating anions (such as triflate). 586 This work clearly reveals the prominent effect of axial ligation on O–O bond scission of the Fe III – m -CPBA adduct of TMP (Scheme 14). Furthermore, Nam and co-workers have reported on the disparities of [(X)(TPFPP)Fe III ]-facilitated (also see Figure 41, section 2.2; X = axial ligand) oxygenation of hydrocarbons using H 2 O 2 as the oxidant, where the feasibility and/or the yields of epoxidation and hydroxylation reactivities were observed to be strongly affected depending on the identity of X.…”
Section: Heme/dioxygen Interactions: From Biology To Model Systemsmentioning
confidence: 75%
“…This intermediate was identified as an 1 A few exceptional cases with much longer bond lengths were also reported, but are attributed to either experimental pitfalls or unconventional data analysis oxoiron(IV) porphyrin cation radical complex, [(TMP c 7)Fe IV (O)] c (1), based on UV-vis [16], NMR [16], Mössbauer [16], EPR [17], resonance Raman (RR) [18,19], and EXAFS [20] spectroscopies. Similar to compounds I of the various enzymes, complex 1 is a cationic complex with an additional axial ligand trans to the oxo ligand.…”
Section: Introductionmentioning
confidence: 99%